2022
DOI: 10.2460/javma.22.03.0101
|View full text |Cite
|
Sign up to set email alerts
|

Pet owners’ and companion animal veterinarians’ perceptions of weight-related veterinarian-client communication

Abstract: OBJECTIVE To compare pet owners’ and veterinarians’ perceptions of veterinarian-client conversations concerning pet weight and identify challenges related to communication about weight. SAMPLE POPULATION Veterinarians (n = 24) and pet owners (27) in southern Ontario, Canada. PROCEDURES 3 veterinarian and 5 pet owner focus groups were conducted with a semistructured interview format. Thematic analysis of verbatim transcripts was conducted. RESULTS Pet owners valued weight as an important health indicator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Just under half of the respondents in the present study agreed that most pet owners with obese pets were not ready to address their pet's weight, which aligns with a previously reported skepticism among veterinarians in relation to clients’ adherence to weight‐management recommendations from the veterinary team 31,32 . This underscores the need for understanding the client's perspective during pet weight‐related conversations, as the present study found veterinary professionals may avoid addressing the status of an overweight or obese pet of a client perceived as ‘difficult’ or ‘resistant’, which is likely to result in the animal not receiving care that is in the best interest of its health and wellbeing.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Just under half of the respondents in the present study agreed that most pet owners with obese pets were not ready to address their pet's weight, which aligns with a previously reported skepticism among veterinarians in relation to clients’ adherence to weight‐management recommendations from the veterinary team 31,32 . This underscores the need for understanding the client's perspective during pet weight‐related conversations, as the present study found veterinary professionals may avoid addressing the status of an overweight or obese pet of a client perceived as ‘difficult’ or ‘resistant’, which is likely to result in the animal not receiving care that is in the best interest of its health and wellbeing.…”
Section: Discussionsupporting
confidence: 79%
“…Participants were less accepting of clients’ use of humour and generally considered it a way to deflect the conversation. Similar perceptions on humour when discussing pet weight were found in a recent qualitative study exploring veterinarians’ perceptions on pet weight‐related communication; veterinarians considered humour to be a useful tool for themselves but did not necessarily appreciate clients’ use of humour and in some cases considered it a barrier to effective communication 32 . Humour was observed to be frequently used by veterinarians in an observational study of feline appointments, which was believed by the researchers to diffuse tension for the veterinarian and client when delivering information about a cat's weight to an apparently resistant client 7 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A small UK study exploring veterinarians’ communication with dog owners about obesity found similar concerns, including perceived issues with client compliance and pet owners' obesity 11 . Recent qualitative research has also indicated that veterinarians may perceive some clients to be unwilling to discuss or consider change to manage their pet's weight 12 …”
Section: Introductionmentioning
confidence: 99%
“…11 Recent qualitative research has also indicated that veterinarians may perceive some clients to be unwilling to discuss or consider change to manage their pet's weight. 12 Environmental factors and feeding management are significant aspects of a pet's nutritional management that relate to obesity. 7,13,14 Owner commitment and engagement in pet weight management is essential to successful weight loss for pets.…”
Section: Introductionmentioning
confidence: 99%